Development and validation of an UV-Vis spectrophotometric method for the quantification of oclacitinib in capsule formulation - Danilo R. O. Momade; Raquel de O. Vilhena; Carolina Castro; Fabiana Regis; Karime Zeraik Abdalla Domingues; Laís Schlichta; Alexandre de Fátima Cobre; Roberto Pontarolo (São Paulo State University (UNESP), 2021)
Objective. The aim of this study was the development and validation of an UV-Vis spectrophotometric method for the quantification of oclacitinib in commercial capsule formulation since pharmacopeias have not yet provided an official monograph for this drug. Methods. The parameters linearity, limit of detection, limit of quantitation, specificity, precision, accuracy, and robustness were determined according to Brazilian and international guidelines. Results. Linearity was determined for the analytical range of 5-15 μg/mL, and a limit of detection of 1.18 μg/mL and limit of quantification of 3.58 μg/mL were obtained. The method was selective and the precision was demonstrated through repeatability and intermediate precision, with relative standard deviations of 1.96% and 1.78%, respectively. In its turn, accuracy presented recovery percentages of 98.32-100.91%. All robustness and sample stability (48 h at 25 °C) results revealed no statistical variation among the groups. Conclusions. The presented method is suitable for the quantification of oclacitinib in commercial capsule formulation.